Tensiones en el desarrollo integral de los niños/as de 3 a 4 años de educación inicial dos etapa I del sector rural del cantón Latacunga - Toaquiza Ayala, Verónica Alejandra (2017)
This project focuses on the causes that generate tensions in the integral development of children's early education. Where the main objective of this research project is to identify tensions in the integral development of children of 3 to 4 years of initial education two stages I of the rural sector of the Latacunga canton, through the analysis of both personal and social factors involved in the Infant personal training to achieve meaningful learning in learners. For the development of this research, the type of methodology that has been used is the deductive, since it has started from acquired valuable data to reach particular conclusions with reference to this issue. It allowed describing the causes by which this phenomenon is used for the acquisition of information by stakeholders, such as, the Director, teachers, parents and children of the educational Occurs....